(untitled) (Historia, 2021)
Harry Wels’ engaging book is a welcome contribution to the growing literature that aims to better understand the development and legacies of wildlife conservation in South Africa. Described not as a biography of Nick Steele, but as seeking to answer the question of "what Nick’s contribution to the establishment of private wildlife conservancies in South Africa was", Wels draws together analyses of wilderness landscapes, the idea of the rhino, the logic of the camp, militarization and technology in the person and life of Nick Steele in productive ways. In his appendix Wels cites Deleuze and Guattari (1980) and the notion of the rhizome as signalling "the thousand plateaus" of people and influence that produced this book. In the same spirit, Wels realises his goal of this book serving as a rhizome itself, opening numerous lines of flight to be taken from cuts into the arguments he articulates.